Penerapan Konseling Dengan Teknik Modeling Simbolis Untuk Menurunkan Tingkat Kebiasaan Merokok Pada Siswa Di SMP - Muliyati, Muliyati (STKIP Andi Matappa, 2018)
This study is a classroom action research that aims to reduce the level of smoking habits through the application of symbolic modeling counseling techniques to students in SMP Negeri 1 Barombong Gowa District on 34 students. Two cycles were performed, the first cycle was held 5 times and the second cycle was 5 meetings. The data retrieval technique uses a questionnaire at each end of the cycle and in-depth observation during counseling with a symbolic modeling technique. The collected data were analyzed by qualitative and quantitative analysis. The results of the study were (1) the average value of smoking habit before counseling with symbolic modeling technique was 48.71 or was in high enough category, (2) the average value of smoking habit after counseling with symbolic modeling technique on cycle 1 is 38.6 or is in the low category, (3) the average value of smoking habit after counseling with the symbolic modeling technique in cycle II is 34.1 or is in very low category, (4) the level of smoking habit among students decrease after applied counseling with method of symbolic modeling at student at SMP Negeri 1 Barombong Gowa regency.